1994
DOI: 10.1002/jmr.300070313
|View full text |Cite
|
Sign up to set email alerts
|

Long‐range interactions between DNA‐bound ligands

Abstract: We have studied the interaction of the A:T specific minor-groove binding ligand 4',6-diamidino-2-phenylindole (DAPI) with synthetic DNA oligomers containing specific binding sites in order to investigate possible long-range interactions between bound ligands. We find that DAPI binds cooperatively to the oligomers. The degree of cooperativity increases with increasing number of binding sites and decreases with the separation between them. This dependence is paralleled by changes in the induced circular dichrois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Cooperativity mediated via conformational changes in DNA has been envisaged with monointercalating drugs such as daunomycin (Krugh et al, 1981;Chaires, 1983;Correia & Chaires, 1994), ethidium (Winkle et al, 1982), actinomycin, and certain anthracenedione derivatives. Cooperative binding of distamycin and DAPI into the minor groove of DNA and synthetic polynucleotides has also been reported (Samuelson et al, 1994). It is entirely possible that cooperative binding of drugs to DNA may be an underlying principle for enhancing their effect on DNA structure and metabolism.…”
Section: Discussionmentioning
confidence: 92%
“…Cooperativity mediated via conformational changes in DNA has been envisaged with monointercalating drugs such as daunomycin (Krugh et al, 1981;Chaires, 1983;Correia & Chaires, 1994), ethidium (Winkle et al, 1982), actinomycin, and certain anthracenedione derivatives. Cooperative binding of distamycin and DAPI into the minor groove of DNA and synthetic polynucleotides has also been reported (Samuelson et al, 1994). It is entirely possible that cooperative binding of drugs to DNA may be an underlying principle for enhancing their effect on DNA structure and metabolism.…”
Section: Discussionmentioning
confidence: 92%
“…The binding of a protein to a single site on nucleosomal DNA is usually not sufficient to promote displacement since it is energetically favorable for the adjacent DNA in the nucleosome to remain bound to histones (57)(58)(59). Protein-induced disruption may occur by ATP-dependent processes or by an energy-independent mechanism when multiple factor binding sites are clustered on the nucleosomal DNA (57)(58)(59)(60)(61)(62). The results in Fig.…”
Section: Figmentioning
confidence: 97%
“…For a series of (A/T) 4 sequences, distamycin demonstrated binding affinities ranging from 0.1 to 1.0 µM (9). Numerous studies have shown that distamycin effectively inhibits DNA cleavage by both nonspecific endonucleases and restriction endonucleases (reviewed in ref 10) and that higher-affinity, multimeric distamycin binding sites exist in heterogeneous DNA (11). Taken together, these findings suggest that distamycin would provide an ideal test for REPSA.…”
mentioning
confidence: 92%
“…This length of random sequence is many times that of an individual distamycin binding site (5 bp). Thus, ST3 allows screening for multimeric distamycin binding sites, which are believed to have higher affinities (11). The flanking sequences were designed to allow interconversion of the IISRE sites, from BpmI to BsgI or Eco57I, depending on the primers used.…”
mentioning
confidence: 99%